Evaluation of the intracellular lipid-lowering effect of polyphenols extract from highland barley in HepG2 cells - Yijun Yao; Zhifang Li; Bowen Qin; Xingrong Ju; Lifeng Wang (Food Science and Human Wellness, 2024)
Active ingredients from highland barley have received considerable attention as natural products for developing treatments and dietary supplements against obesity. In practical application, the research of food combinations is more significant than a specific food component. This study investigated the lipid-lowering effect of highland barley polyphenols via lipase assay in vitro and HepG2 cells induced by oleic acid (OA). Five indexes, triglyceride (TG), total cholesterol (T-CHO), low density lipoprotein-cholesterol (LDL-C), aspartate aminotransferase (AST), and alanine aminotransferase (ALT), were used to evaluate the lipid-lowering effect of highland barley extract. We also preliminary studied the lipid-lowering mechanism by Real-time fluorescent quantitative polymerase chain reaction (qPCR). The results indicated that highland barley extract contains many components with lipid-lowering effects, such as hyperoside and scoparone. In vitro, the lipase assay showed an 18.4 % lipase inhibition rate when the additive contents of highland barley extract were 100 µg/mL. The intracellular lipid-lowering effect of highland barley extract was examined using 0.25 mM OA-induced HepG2 cells. The results showed that intracellular TG, LDL-C, and T-CHO content decreased by 34.4 %, 51.2 %, and 18.4 %, respectively. ALT and AST decreased by 51.6 % and 20.7 % compared with the untreated hyperlipidemic HepG2 cells. qPCR results showed that highland barley polyphenols could up-regulation the expression of lipid metabolism-related genes such as PPARγ and Fabp4.